Guideline Recommended Medical Therapy for Cardiovascular Diseases in the Obese: Insights From the Veterans Affairs Clinical Assessment, Reporting, and Tracking (CART) Program. Issue 5 (May 2016) - Valle, Javier A.; O'Donnell, Colin I.; Armstrong, Ehrin J.; Bradley, Steven M.; Maddox, Thomas M.; Ho, P. Michael
Abstract : Background: Stigma against the obese is well described in health care and may contribute to disparities in medical decision‐making. It is unknown whether similar disparity exists for obese patients in cardiovascular care. We evaluated the association between body mass index (BMI) and prescription of guideline‐recommended medications in patients undergoing elective percutaneous coronary intervention. Methods and Results: Using data from the Veterans Affairs Clinical Assessment, Reporting, and Tracking System Program, we identified patients undergoing elective percutaneous coronary intervention from 2007 to 2012, stratifying them by category of BMI. We described rates of prescription for class I guideline recommended medications for each BMI category (normal, overweight, and obese). Multivariable logistic regression assessed the association between BMI category and medication prescription. Seventeen thousand thirty‐seven patients were identified, with 35.3% having overweight BMI, and 50.8% obese BMI. Obese patients were more likely than normal BMI patients to be prescribed β‐blockers (OR 1.34), statins (OR 1.39), or ACE/ARB (odds ratio [OR] 1.52; all significant) when indicated. Overweight patients were more likely than normal BMI patients to be prescribed statins (OR 1.29) and angiotensin‐converting enzymes/angiotensin II receptor blockers (OR 1.41) when indicated. There was no association between BMI category and prescription of anticoagulants. Conclusions: Over 85% of patients undergoing elective percutaneous coronary intervention in the Veterans Affairs are overweight or obese. Rates of guideline‐indicated medication prescription were <70% among all patients, and across BMI categories, with an association between increased BMI and greater use of guideline‐recommended medications. Our findings offer a possible contribution to the obesity paradox seen in many cardiovascular conditions.